An elevated amniotic fluid prostaglandin F2α concentration is associated with intra-amniotic inflammation/infection, and clinical and histologic chorioamnionitis, as well as impending preterm delivery in patients with preterm labor and intact membranes. (17th August 2016) - Park, Jee Yoon; Romero, Roberto; Lee, JoonHo; Chaemsaithong, Piya; Chaiyasit, Noppadol; Yoon, Bo Hyun
Abstract: Objective: To determine whether an elevated amniotic fluid concentration of prostaglandin F2α (PGF2α ) is associated with intra-amniotic inflammation/infection and adverse pregnancy outcomes in patients with preterm labor and intact membranes. Materials and methods: The retrospective cohort study included 132 patients who had singleton pregnancies with preterm labor (< 35 weeks of gestation) and intact membranes. Amniotic fluid was cultured for aerobic and anaerobic bacteria as well as for genital mycoplasmas. Intra-amniotic inflammation was defined by an elevated amniotic fluid matrix metalloproteinase-8 (MMP-8) concentration (>23 ng/mL). PGF2α was measured with a sensitive and specific immunoassay. The amniotic fluid PGF2α concentration was considered elevated when it was above the 95th percentile among pregnant women at 15–36 weeks of gestation who were not in labor (≥170 pg/mL). Results: (1) The prevalence of an elevated amniotic fluid PGF2α concentration was 40.2% (53/132) in patients with preterm labor and intact membranes; (2) patients with an elevated amniotic fluid PGF2α concentration had a significantly higher rate of positive amniotic fluid culture [19% (10/53) versus 5% (4/79); p = 0.019], intra-amniotic inflammation/infection [49% (26/53) versus 20% (16/79); p = 0.001], spontaneous preterm delivery, clinical and histologic chorioamnionitis, and funisitis, as well as a higher median amniotic fluid MMP-8 concentration and amniotic fluid white blood cell count and a shorter amniocentesis-to-delivery interval than those without an elevated concentration of amniotic fluid PGF2α ( p < 0.05 for each); and (3) an elevated amniotic fluid PGF2α concentration was associated with a shorter amniocentesis-to-delivery interval after adjustment for the presence of intra-amniotic inflammation/infection [hazard ratio 2.1, 95% confidence interval (CI) 1.4–3.1; p = 0.001]. Conclusion: The concentration of PGF2α was elevated in the amniotic fluid of 40.2% of patients with preterm labor and intact membranes and is an independent risk factor for intra-amniotic inflammation/infection, impending preterm delivery, chorioamnionitis, and funisitis.